A longitudinal investigation of third-person subject expression in additional-language Spanish - Gudmestad, Aarnes; Metzger, Thomas (Borealis – An International Journal of Hispanic Linguistics, 2025)
The goal of the present investigation was to examine the variable use of third-person subject forms in additional-language Spanish over a period of 21 months that included an academic year in Spain or Mexico. The data came from the additional-language learners of Spanish in the LANGSNAP corpus (N = 27). We analyzed production data from three points in time: before the participants went abroad, at the end of their nine-month stay, and nine months after the sojourn abroad ended. We coded all contexts of third-person subject forms (K = 9,379) for the subject form used, seven linguistic variables, and five extralinguistic variables. The analysis revealed that learners used a diverse inventory of subject forms, namely unexpressed subjects, five types of pronouns, lexical noun phrases, and verbal phrases. The mixed-effects model demonstrated that learners’ variable use of third-person subjects is complex. In brief, four linguistic factors (referent continuity, clause type, specificity, and perseveration) and one extralinguistic factor (task) predicted use. We moreover observed stability in their use of third-person subject forms over time, meaning that no significant changes occurred while learners were abroad.
Keywords: subject expression; SLA; Spanish; study abroad; variation